Enhancing Employee Performance: Insights from Training and Evaluation in Bhojpur District Government Offices - Katuwal, Chandan (Sahayaatra सहयात्रा, 2024)
Employees are the lifeblood of any company. The effectiveness of the company's workforce determines whether it succeeds or fails. The article offers a concise assessment of the literature on the benefits of training and evaluation insights for enhancing employee performance. This paper examined how training and evaluation criteria and practices affect the employee performance of the government employees of Bhojpur district headquarters and offered recommendations for how government offices might boost employee performance through efficient training initiatives and prudent performance evaluation practices. The study's methodology is in line with mixed research designed with a descriptive-analytical approach examining the literature and several empirical studies on the efficacy of training and performance evaluation in enhancing employee performance, as well as the rigorous analysis of the surveyed data on the employees of government offices in Bhojpur District. The findings highlight the need for organizations to develop training programs that address key areas for improvement, while also ensuring accessibility and relevancy. Moreover, organizations should strive to establish effective evaluation systems that provide regular feedback, clear criteria, and a balance between subjective and objective measures. The paper offers suggestions for the bureaucrats to assess employee performance and find out the true causes of the performance problem so the problem can be solved in time by incorporating desired training programs and flexible yet modern performance evaluation practices.